Effects of Defects on the Temperature‐Dependent Thermal Conductivity of Suspended Monolayer Molybdenum Disulfide Grown by Chemical Vapor Deposition. (23rd October 2017) - Yarali, Milad; Wu, Xufei; Gupta, Tushar; Ghoshal, Debjit; Xie, Lixin; Zhu, Zhuan; Brahmi, Hatem; Bao, Jiming; Chen, Shuo; Luo, Tengfei; Koratkar, Nikhil; Mavrokefalos, Anastassios
Abstract: It is understood that defects of the atomic arrangement of the lattice in 2D molybdenum disulfide (MoS2 ) grown by chemical vapor deposition (CVD) can have a profound effect on the electronic and optical properties. Beyond these it is a major prerequisite to also understand the fundamental effect of such defects on phonon transport, to guarantee the successful integration of MoS2 into the solid‐state devices. A comprehensive joint experiment‐theory investigation to explore the effect of lattice defects on the thermal transport of the suspended MoS2 monolayer grown by CVD is presented. The measured room temperature thermal conductivity values are 30 ± 3.3 and 35.5 ± 3 W m −1 K −1 for two samples, which are more than two times smaller than that of their exfoliated counterpart. High‐resolution transmission electron microscopy shows that these CVD‐grown samples are polycrystalline in nature with low angle grain boundaries, which is primarily responsible for their reduced thermal conductivity. Higher degree of polycrystallinity and aging effects also result in smoother temperature dependency of thermal conductivity (κ) at temperatures below 100 K. First‐principles lattice dynamics simulations are carried out to understand the role of defects such as isotopes, vacancies, and grain boundaries on the phonon scattering rates of our CVD‐grown samples. Abstract : The lattice structure–thermal conductivity relation of MoS2 monolayer grown by chemical vapor deposition is investigated in a wide temperature range using a suspended microdevice with integrated resistance thermometers. Higher degree of polycrystallinity leads to smoother temperature dependency at temperatures below 100 K. The observations are explained by the first‐principles lattice dynamics calculations.